THE IMPACT OF MOBILE PHONE IN LEARNING - Jakhongir Buriboev; Yuldosheva Kamola (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This study delves into the influence of mobile phones on classroom  learning. Mobile  phones,  enabling  learning  anytime  and  anywhere,  have  enhanced communication  and  boosted  student  motivation,  making  them  valuable  tools  in education.  However,  challenges  such  as distraction  and  academic  misconduct have emerged.  To  mitigate  these  issues,  school  administrators  actively  monitor  mobile phone usage in classrooms. This article examines key principles and challenges related to the integration of mobile phones into lessons. It also offers personal insights on effectively incorporating these devices. The primary aim of this research is to analyze how educators and leaders address the duality of mobile technology in education. While digital natives exhibit strong positive attitudes towards technology and possess basic technical skills, they often  lack  proficiency  in  advanced,  classroom-specific  applications.  As  educators increasingly explore the integration of mobile phones in teaching, they evaluate both the opportunities and obstacles associated with this technology.